Reviews - Derek Law; Chris Foggin; Nora Mogey; Louisa Yong; Philip Barker (Association for Learning Technology, 2003)
Peter Jarvis is Professor of Continuing Education at the University of Surrey and a distinguished authority in this field. In this work he attempts to analyse what constitutes a 'real university' and whether the social changes which have impacted on traditional universities and the growth of other types of university represent a crisis and/or a failure to meet societal needs. Corporate universities have grown into a major business because the traditional university failed to meet the demands of corporate business for education and training. He stresses the need for universities to be true to their own identity in the face of such pressure.